PENGARUH KEPUASAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL GRAN MELIA JAKARTA - Chaterina Yunita Tarigan; Rio Anggara (LPPM Universitas Asa Indonesia, 2017)
Purpose- This study aims to determine the job satisfaction, motivation and dicipline affect simultaneously and partially to employee performance Design/methology/approach- The population in this research is Employee at Hotel Gran Melia Jakarta. The sample used in this study is the employee of 100 people, sampling technique used is the accidental sampling. Data analysis tools used in this research are multiple linear regression, validity test, reliability test, classical assumption test (normality test, multicolinearity test, heteroscedasticity test, and linearity test). While testing hypothesis include test F, t test, and partial correlation analysis and coefficient of determination (R2). Findings- From the analysis can be seen that job satisfaction, motivation and dicipline have an influence on employee performance partially or simultaneously.